SUPPORT OF A HIGHER EDUCATION INSTITUTION FOR THE NEW TEACHERS - Baltusite, Regina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the problem of the support of a higher education institution for the new teachers. The professional development is a complex and time-consuming processof a personality’s self-perfection, self-development and self-training. The process of professional development begins with the obtaining of a diploma. The success in the professional activities and the progress in making a career depend on a person him/herself in various aspects. However, irrespective of the fact that a beginning teacher has the experience of practice, when starting professional activities in the respective working environment, he/she faces situations that demand immediate solution of a problem, but there is not always a person beside a beginning teacher, who could provide support regarding dealing with a particular situation and making a decision. The support, provided by a higher education institution, when a new teacher starts working, is very important. A beginning teacher can use the contacts established at the higher education institution and apply to the university lecturers for assistance.